Rally for Normative Demands and Solidarity of Workers - Pradhanawati, Ari (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
This research is initiated by an interesting fact that there are still many labor strikes and rallies in Indonesia. The purpose of this study is to determine: the influence of normative demands and solidarity together on job dissatisfaction of workers. This research is intended as explanatory research. Sampling method used in this research is accidental sampling. The sample consists of 100 workers/laborers who joined rallies on May 1, 2014. The results show on the indicator the amount of City Minimum Wage Rates in normative demands variable, respondents believe the amount of wages earned are still not in accordance with the provisions of the minimum wage set by the government. Participation of workers in the fight for economic security must be done in various ways including demonstrations, based on solidarity between workers in order to put pressure on policy makers with regard to labor issues. In conclusion, good normative demands in accordance with the provisions of the agreement and the strong solidarity between workers will reduce dissatisfaction. Suggestions are made on normative demands variable; review should be made on the amount of the city minimum wage rates; leave entitlements, workers social security and dismissal policies should be in compliance with the current government policy.